Optimization of Indirect Fracturing Process Parameters Based on Mechanical Properties of Fractured and Low-Permeability Coal - Wenfeng Yuan; Xigui Zheng; Niaz Muhammad Shahani (Geofluids)
The coal-bed methane (CBM) resources in soft and low-permeability coals are assumed to be as much as 15 × 1012 m3 in China. Indirect fracturing technology can be an effective method to successfully extract methane within soft coals. The key to the success of this technique is to optimize the parameters, such as water injection flow rate and fracture initiation location, so that the hydraulic fracturing parameters enable the fractures to pass through the interface between coal and rock and propagate sufficiently into the coal. This paper focuses on solving the above problems by focusing on discontinuities and plastic characteristics of soft coals. Voronoi polyhedron was used to simulate the discontinuities of coal, and the constitutive relations of ductile fracture-seepage and elastoplastic damage-seepage are, respectively, given to the discontinuities and coal matrix. A numerical model was established based on the above theory to simulate the effect of stress difference Δσ, coal-rock interface friction coefficient fc,r, water injection flow rate iw, and distance between the well and the interface Dop on indirect fracturing fractures. The results show that the HFs area in the coal is positively correlated with Δσ, fc,r, and iw, and it first increases and then decreases with the decrease of Dop. The above results were applied in the Zhaozhuang mine of Qinshui Basin by optimizing Dop = 1 m and iw = 8 m3/min, so that CBM production has been greatly increased. The results can provide theoretical support for the efficient development of CBM in fractured and low-permeability coal seam areas.